Knowledge on Puerperal Sepsis among Hospitalized Postnatal Mothers in a Lumbini Provincial Hospital - Kausal, Sabita; Dangol, Bhuwan Kumari (Journal of Nursing Education of Nepal, 2022)
Introduction: Puerperal sepsis is a leading cause of maternal mortality and morbidity in developing countries due to the lack of knowledge on preventive measures. The objective of the study was to find out the knowledge on puerperal sepsis among hospitalized postnatal mothers. Method: A descriptive cross-sectional research design was adopted among 262 postnatal mothers who were admitted in Lumbini Provincial Hospital. Data were collected by using non-probability purposive sampling technique, through structured interview schedule. Data was analyzed by using descriptive and inferential statistics. Result: More than one third of respondents (38.2%) were from the age group 25-29 years with mean age was 26.21+4.44. Only 19.1% had good level of knowledge on puerperal sepsis.There was statistical association between level of knowledge on puerperal sepsis and ethnicity (p=0.006), educational level (p<0.001) and number of antenatal checkup (p=0.012). Conclusion: The majority of the respondents had fair level of knowledge on puerperal sepsis. However, only few respondents had known the important issue regarding the risk factors such as prolonged labour, sexual intercourse in late pregnancy and anemia. There is need to increase awareness program for antenatal as well as postnatal mothers that would help to promote healthy postpartum period. Keywords: Post-partum Period, Puerperal sepsis